Solving university course timetabling problem using linear programming model / Nurul Liyana Abdul Aziz ... [et al.] - Abdul Aziz, Nurul Liyana; Sukri, Nurhafizati; Mazlan, Midhati Auni; Adam, Nur Hamizah (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2022)
The process of allocatingtimeand resourcesto each operation oractivity is known astimetabling. This study focused on the educational timetabling problem and utilized a linear programming method to build feasible timetables for all tutorial classes taken by various student groups. The goal of this study is to maximize allocation preference of classes to timeslot and employ the integer linear programming model for solving a course timetabling problem for a university. Data is taken from the study in a Tunisian University, as described by Dammak et al.(2008).